Challenges and Implications in the Context of Law and Citizenship Identity in Indonesia - Maizul Habibah, Siti (Journal of Law and Humanity Studies, 2025)
The practice of dual citizenship poses a variety of complex challenges for the individuals and countries involved. From an individual perspective, dual citizenship can lead to identity conflicts, legal uncertainty, and administrative difficulties. Instead, the country faces challenges in establishing proper legal jurisdiction, promoting effective international cooperation, and maintaining national security. Indonesia, for example, adopted a strict approach to dual citizenship by insisting that citizens should choose only one citizenship. While there are some exceptions, this approach reflects efforts to maintain state sovereignty and reduce potential legal and identity conflicts. In facing these challenges, it is important to pay attention to individual rights, maintain national security, and promote international cooperation.